(untitled) (Baghdad Science Journal, 2025)
The alloys of CdSe1-xTex compound have been prepared from their elements successfully with high purity (99.9999%) which mixed stoichiometry ratio (x=0.0, 0.25, 0.5, 0.75 and 1.0) of (Cd, Se and Te) elements. Films of CdSe1-xTex alloys for different values of composition with thickness(0.5?m) have been prepared by thermal evaporation method at cleaned glass substrates which heated at (473K) under very low pressure (4×10-5mbar) at rate of deposition (3A?/s), after that thin films have been heat treated under low pressure (10-2mbar) at (523K) for two hours. The optical studies revealed that the absorption coefficient (?) is fairly high. It is found that the electronic transitions in the fundamental absorption edge tend to be allowed direct transition. It was also found that the optical energy gap vary non-linearly with composition (x) and have a minimum value at x=0.5 and increases after heat treatment. It is found that the optical constants vary non-linearly with composition, and the behavior inverse at x=0.5, and affected by heat treatment. The behavior of ?1 is similar to the behavior of n, while the behavior of ?2 is similar to the behavior of k.